2020
DOI: 10.1039/c9nj06346c
|View full text |Cite
|
Sign up to set email alerts
|

An unorthodox metal-free synthesis of dihydro-6H-quinoline-5-ones in ethanol/water using a non-nucleophilic base and their cytotoxic studies on human cancer cell line

Abstract: One-pot metal-free catalysed green methodology for dihydro-6H-quinoline-5-ones and their biological activities in HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Encouraged by this reaction outcome, we further optimized the reaction by adding TBAB : oxalic acid (1 : 1 (100 : 100 mg)) DES to step 2, leading to an increased product yield of 52% (Table 1, entry 12). Based on this result, the reactions were further explored using TBAB-based DESs such as TBAB : tartaric acid (1 : 1), TBAB : citric acid (1 : 1), TBAB : ethylene glycol (1 : 1), TBAB : succinic acid (1 : 1), TBAB : sucrose (1 : 1), TBAB : glycerol (1 : 1) and TBAB : PTSA (1 : 1) (Table 1, entries [13][14][15][16][17][18][19]. From these trials, we have observed that a 58% yield of product 4A was achieved using the TBAB : PTSA (1 : 1) DES ( 1, entries 23-27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by this reaction outcome, we further optimized the reaction by adding TBAB : oxalic acid (1 : 1 (100 : 100 mg)) DES to step 2, leading to an increased product yield of 52% (Table 1, entry 12). Based on this result, the reactions were further explored using TBAB-based DESs such as TBAB : tartaric acid (1 : 1), TBAB : citric acid (1 : 1), TBAB : ethylene glycol (1 : 1), TBAB : succinic acid (1 : 1), TBAB : sucrose (1 : 1), TBAB : glycerol (1 : 1) and TBAB : PTSA (1 : 1) (Table 1, entries [13][14][15][16][17][18][19]. From these trials, we have observed that a 58% yield of product 4A was achieved using the TBAB : PTSA (1 : 1) DES ( 1, entries 23-27).…”
Section: Resultsmentioning
confidence: 99%
“…13 Likewise, in 2013 the same group revealed a one-pot oxidative synthesis of dihydropyridines utilizing 1,3-dicarbonyls, aldehydes, ketones, and ammonium carbonate with the combination of H 2 O 2 /MSPA-10 as a catalyst, 14 Furthermore, Kundu et al reported the synthesis of dihydroquinolinones from β-chloro-α,β-unsaturated aldehydes and 1,3-dicarbonyls using DABCO as a base and a mixture of ethanol : H 2 O (1 : 1) as a solvent (Scheme 1a). 15 Additionally, α-alkenylation of ketones and C(sp 3 )-H functionalization of 2-methyl azaarenes was achieved using a series of transition-metal catalysts, listed in Scheme 1b. [16][17][18][19][20] Although these methods described in the literature are broadly effective and successful, some of them still face challenges, in terms of lengthy multi-step protocols, environmentally harmful reaction conditions, limited diversity of the starting materials, costly metal catalysts and the utilization of volatile organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…. 17 This compound was synthesized according to general procedure 1. Crude 3c was purified by flash column chromatography on silica gel (petroleum ether/ethyl acetate 10:1), affording the product in 68% yield (33 mg) as a white solid.…”
Section: -(4-fluorophenyl)-78-dihydroquinolin-5(6h)-one (3c)mentioning
confidence: 99%
“…For instance, Kantevari and co-workers 4 tested different derivatives of 2-aryl-7,8-dihydroquinolin-5(6 H )-ones against Mycobacterium tuberculosis­ strain H37Rv, with compound 1 being the most potent with a MIC of 1.56 μg/mL. Valderrama and co-workers 5 tested different 2-aryl-7,8-dihydroquinolin-5(6 H )-ones bearing quinones, such as 2 , as antitumor agents, whereas Dhara and co-workers 6 synthesized 2-aryl-7,8-dihydroquinolin-5(6 H )-ones, such as 3 , that were proven to be cytotoxic in different cell lines. Also, this moiety can be derivatized into other compounds, as reported by Kantevari and co-workers, 7 in which they synthesized miscellaneous 2-aryl-7,8-dihydroquinolin-5(6 H )-ylidenehydrazinecarbothioamides, such as 4 , and it was determined to be more potent as antitubercular than the parent 2-aryl-7,8-dihydroquinolin-5(6 H )-one derivative (Figure 1 ).…”
Section: Table 1 Ic 50 Valu...mentioning
confidence: 99%